Transformasi Karakter Pemimpin dalam Kedewasaan Iman 2 Timotius 2:2 di Gereja JKI The Rock Tangerang Selatan - Novi Puji Kurniawan; Asep Afaradi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the transformation of leader character as a key factor in achieving faith maturity within JKI The Rock. Grounded in 2 Timothy 2:2, the research explores how the chain discipleship (mentoring) model contributes to spiritual growth, leadership quality, and the continuity of the church’s mission. A qualitative methodology was employed, using an exegetical approach combined with an organizational case study. The findings reveal that faith maturity is not developed individually but through a continuous process of mentoring, where values, spiritual integrity, and leadership character are transmitted from proven leaders to future generations of faithful leaders. This process strengthens spiritual stability and prepares leaders who are capable of carrying out ministry responsibilities effectively. The study concludes that JKI The Rock needs a structured leadership development system that prioritizes both faithfulness and competence. Such a system is essential to ensure sustainable leadership regeneration and the long-term effectiveness of the church’s mission and ministry.